2005
DOI: 10.1111/j.1464-5491.2005.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for asymptomatic bacteriuria in women with Type 2 diabetes mellitus

Abstract: Women with Type 2 diabetes are not at higher risk of developing ASB than non-diabetic women. Independent and significant risk factors for ASB are macroalbuminuria and serum creatinine. The low prevalence of ASB found in this study may be as a result of the ethnic origin of these women and the circumcised state of their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
36
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
11
36
2
1
Order By: Relevance
“…26,27 In our study also ASB had a statistically significant association with proteinuria with p<0.05. 20 also showed that macroalbuminuria was an independent and significant risk factor for ASB in type 2 Diabetes Mellitus women which was reiterated by our study as well…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…26,27 In our study also ASB had a statistically significant association with proteinuria with p<0.05. 20 also showed that macroalbuminuria was an independent and significant risk factor for ASB in type 2 Diabetes Mellitus women which was reiterated by our study as well…”
Section: Discussionsupporting
confidence: 66%
“…In agreement to our results, Sunnesh Reddy et al and Nicolle LE et al in their study had also showed that patients with long standing diabetes mellitus had increased risk of ASB; however, Ishay et al in their study did not find any association between these two. 13,19,20 Collee JG et al in their study stated uncontrolled blood sugar level as an important risk factor for ASB in diabetic patient. 21 The high prevalence of ASB among diabetics in our study may be due to uncontrolled blood sugar level.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 The prevalent microorganisms (Table 2) in the present study were coagulase negative Staphylococcus (36.3%), Klebsiella sp (15.9%), Candida sp (13.7%), E. coli and Serratia sp (10.8% each). This is contrary to other studies 5,7,8,9 where E. coli was the predominant bacteria. The predominance of bacteria other than E. coli in the urinary tract is increasingly being reported.…”
Section: Discussioncontrasting
confidence: 55%
“…5,6,7 On the contrary, another study 8 reported no significant difference in the prevalence of ASB between diabetic women and non-diabetic women (P = 0.07).…”
Section: Introductionmentioning
confidence: 68%
“…This was unlike what Ishay A et al described in 2006, who found serum creatinine as an independent risk factor for ASB. 14 Diabetic patients with Nephropathy had 3.5 times risk of getting ASB as compared with patients who had no nephropathy. However, this figure was not statistically significant (95%, CI = .681 -18.387).…”
Section: Discussionmentioning
confidence: 92%